Nanosized TiO2-induced reproductive system dysfunction and its mechanism in female mice. - Xiaoyang Zhao (Public Library of Science (PLoS), 2013)
Recent studies have demonstrated nanosized titanium dioxide (nano-TiO2)-induced fertility reduction and ovary injury in animals. To better understand how nano-TiO2 act in mice, female mice were exposed to 2.5, 5, and 10 mg/kg nano-TiO2 by intragastric administration for 90 consecutive days; the ovary injuries, fertility, hormone levels, and inflammation-related or follicular atresia-related cytokine expression were investigated. The results showed that nano-TiO2 was deposited in the ovary, resulting in significant reduction of body weight, relative weight of ovary and fertility, alterations of hematological and serum parameters and sex hormone levels, atretic follicle increases, inflammation, and necrosis. Furthermore, nano-TiO2 exposure resulted in marked increases of insulin-like growth factor-binding protein 2, epidermal growth factor, tumor necrosis factor-α, tissue plasminogen activator, interleukin-1β, interleukin -6, Fas, and FasL expression, and significant decreases of insulin-like growth factor-1, luteinizing hormone receptor, inhibin α, and growth differentiation factor 9 expression in mouse ovary. These findings implied that fertility reduction and ovary injury of mice following exposure to nano-TiO2 may be associated with alteration of inflammation-related or follicular atresia-related cytokine expressions, and humans should take great caution when handling nano-TiO2.